Determinants Of Amount Home Ownership Loans In South Sulawesi - Rifki Khoirudin (AKUNTANSI DEWANTARA, 2022)
This research aims to determine the effect of economic growth, loan interest rates, loan to deposit ratios, loan to value, and inflation on the number of mortgage loans in South Sulawesi, this type of research is secondary obtained from the Centra Statistics Agency, Bank Indonesia, and the Financial Services Authority. The data analysis technique used is multiple linear regression analysis, the results of the study show that loan to deposit ratio an loan to value have a positive and significant effect on housing loans in South Sulawesi, loan interest rates have a negative and significant effect on housing loans in South Sulawesi, while economic growth and inflation do not affect housing loans in South Sulawesi, it is hoped that when setting loan interest rates more consider the surrounding economic conditions and are expected to continue to observe the loan to deposit ratio so that funds can be channeled optimally, and it is hoped that the loan to value policy will continue to have the desire to apply for home ownership loans.